Professional military education : a cross-cultural survey - Jalili,Duraid; Annen,Hubert (Berlin : Peterlang Pub, 2019)
This book brings together non-Western viewpoints on military pedagogy and professional military education. It contains essays on subjects including large-scale educational reform, civil-military and academic influences on military pedagogy, internationalisation, cross-cultural collaboration, and interoperability within military education.
Keywords: Education & Training; Professional Development; Social Psychology